Moderasi Struktur Aset dan Likuiditas Pada Pengaruh Struktur Modal pada Profitabilitas di Perusahaan Property dan Real Estate - Andriyani, Ni Kadek Yani; Dwirandra, A.A.N.B (E-Jurnal Akuntansi, 2023)
The aim of this research is to determine the moderation of asset structure and liquidity on the influence of capital structure on profitability. The location of this research was carried out at Property and Real Estate Companies Listed on the Indonesia Stock Exchange 2017-2019. This research data uses secondary data. This research sample was taken using a nonprobability sampling method using purposive sampling technique. The data analysis technique used in this research is moderated regression analysis technique. The results of this research indicate that asset structure has a positive effect on profitability. Asset structure strengthens the positive influence of capital structure on profitability. Liquidity weakens the positive influence of capital structure on profitability. Keywords: Asset Structure; Liquidity; Capital Structure; Profitability